TRENDS OF ELDERLY FAMILY SOCIAL TRANSFORMATION AS ADAPTATION TO CURRENT CONDITIONS IN RUSSIA - Lana I. Sementsova; Lyudmila S. Nikolayeva (Advanced Engineering Research)
The problems of the elderly family social transformation in Russia as the adaptation to the cur rent changes are co nsidered. Difficulties in solving the adaptation problems of an elderly family, the specificity and f eatures of an elderly couple under the social changes in Russia are revealed.